(untitled) (Eurasian Scientific Herald, 2023)
It is highlighted in the study that digital transformations of the fourth industrial revolution are changing the modern human world, encouraging a person to acquire new competencies and become a qualified specialist in the digital economy. In connection with the progressive scientific and technical development, the institute of higher education is being transformed; new previously unknown approaches to the organization of higher education appear. One of such approaches is the introduction of online learning in higher education. The authors refer to the experience of 2020, when, during the pandemic of the new coronavirus infection, the whole world began to actively transfer work processes to a remote format, which also affected the institute of education